ANALISIS PENERAPAN PPN DAN PPH PASAL 22 ATAS PENGADAAN BARANG PADA KANTOR BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN PERWAKILAN SULAWESI UTARA - Mufarokhah, Arifatul; Sondakh, Jullie J.; Pangerapan, Sonny (Universitas Sam Ratulangi, 2018)
The treasurer as functional officer has the obligation to deposit and report the tax payable. Examples of taxes that must be deposited and reported by the treasurer are Value Added Tax and Tax Article 22 in the activities of procurement of goods. Procurement of goods for the government is a process of activities to meet or provide the needs and supply of goods for central and local governments. The purpose of this study is to know how to calculate, deposit, and report Value Added Tax and Income Tax Article 22 on Procurement of Goods at Kantor Badan Pengawasan Keuangan dan Pembangunan Perwakilan Sulawesi Utara. This research method using qualitative descriptive method. The result of the research shows that the calculation of Value Added Tax is subject to 10% tariff and for Tax of Article 22 is charged 1.5% tariff then deposited using billing code to Bank BNI. Calculation of VAT and Income Tax Article 22 in 2017 at Kantor Badan Pengawasan Keuangan dan Pembangunan Perwakilan Sulawesi Utara is in conformity with the applicable law, but there are still some calculations performed by the treasurer that is not appropriate. In the case of reporting the treasurer does not report, the treasurer should conduct tax reporting in accordance with the rules stipulated by the Minister of Finance and the Directorate General of Taxes in order not to be subject to sanctions on tax administration.Keywords : Calculation, Deposit, Reporting, Value Added Tax, Income Tax Article